Discourse Markers in Bahasa Indonesia: The Use and The Meaning - Nugraha Krisdiyanta (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2020)
Bahasa Indonesia has a lot discourse markers. This paper tries to find the use and the meaning of discourse markers in Bahasa Indonesia which appear in the initial position. The data are gathered from the movie entitled “3 Dara”. The research employed Schiffrin’s theory in discourse markers: must be detachable, contextualization cues and multifunction. The findings show that the markers are mostly to emphasize the intention of the speakers. The markers exist to make the conversation go smoothly and naturally. Most of the discourse markers do not have semantic meaning but they have ‘meaning’ in the conversation especially in the intention of the speakers. Some are to emphasize the points that the speaker wants to, others are to make the conversation go smoothly, and some are to function as hedges. Those markers are important in the conversation despite of their meaning. Without markers, conversation will be dull and boring.